2018
DOI: 10.1128/msphere.00545-18
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of NDT80 Family Transcription Factors in Candida albicans Using New CRISPR-Cas9 Approaches

Abstract: Transcription factors play key roles in regulating virulence of the human fungal pathogen C. albicans. In addition to regulating the expression of virulence factors, they also control the ability of C. albicans to switch to filamentous hyphal growth, which facilitates biofilm formation on medical devices and invasion into tissues. We therefore used new CRISPR/Cas9 methods to examine the effects of deleting three C. albicans genes (NDT80, REP1, and RON1) that encode transcription factors with similar DNA bindin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 47 publications
3
49
2
Order By: Relevance
“…This result is in contrast to the findings in a recent study, where the deletion of RON1 using the CRISPR/Cas9 method did not affect filamentous growth in response to GlcNAc [28]. However, other phenotypes were indeed observed for the ron1/ron1 mutant strain in this study that were consistent with its role in GlcNAc catabolism [28]. Moreover, the ndt80/ndt80 ron1/ron1 double mutant strain exhibited increased filamentation in the presence of GlcNAc.…”
Section: Glcnac Catabolismcontrasting
confidence: 99%
See 2 more Smart Citations
“…This result is in contrast to the findings in a recent study, where the deletion of RON1 using the CRISPR/Cas9 method did not affect filamentous growth in response to GlcNAc [28]. However, other phenotypes were indeed observed for the ron1/ron1 mutant strain in this study that were consistent with its role in GlcNAc catabolism [28]. Moreover, the ndt80/ndt80 ron1/ron1 double mutant strain exhibited increased filamentation in the presence of GlcNAc.…”
Section: Glcnac Catabolismcontrasting
confidence: 99%
“…Another transcription factor, Ron1, was discovered to regulate GlcNAc catabolism and GlcNAc-induced filamentous growth in C. albicans [24]. This result is in contrast to the findings in a recent study, where the deletion of RON1 using the CRISPR/Cas9 method did not affect filamentous growth in response to GlcNAc [28]. However, other phenotypes were indeed observed for the ron1/ron1 mutant strain in this study that were consistent with its role in GlcNAc catabolism [28].…”
Section: Glcnac Catabolismcontrasting
confidence: 78%
See 1 more Smart Citation
“…Subsequent rounds of marker recycling enable the deletion of multiple genes within a single strain using only 2 marker types. It is also possible to use traditional recyclable markers as repair constructs in CRISPR-based deletion schemes [17].…”
Section: Crispr/cas9 Cuts the Time To A C Albicans Double Mutant Bymentioning
confidence: 99%
“…In addition, as described above, a mutant that cannot catabolize GlcNAc can be stimulated by GlcNAc to form hyphae without obvious induction of hyphal-specific genes [23]. Other studies have shown that some transcription key factors needed for hyphal growth can be bypassed under special conditions [59][60][61]. Thus, although it is clear that transcriptional regulation is required to make cells competent to be induced to form hyphae, there is no clear evidence at this point that the hyphal-induced genes promote hyphal growth, which has led to development of alternative models, such as translational regulation [57].…”
Section: Hyphal-induced Genes Do Not Play An Obvious Role In Hyphal Mmentioning
confidence: 99%